Independent origins of loss-of-function mutations conferring oxamniquine resistance in a Brazilian schistosome population() - Chevalier, Frédéric D. (Int J Parasitol, 2016)
Molecular surveillance provides a powerful approach to monitoring the resistance status of parasite populations in the field and for understanding resistance evolution. Oxamniquine (OXA) was used to treat Brazilian schistosomiasis patients (mid-1970s to mid-2000s) and several cases of parasite infections resistant to treatment were recorded. The gene underlying resistance (SmSULT-OR) encodes a sulfotransferase required for intracellular drug activation. Resistance has a recessive basis and occurs when both SmSULT-OR alleles encode for defective proteins. Here we examine SmSULT-OR sequence variation in a natural schistosome population in Brazil ~40 years after the first use of this drug. We sequenced SmSULT-OR from 189 individual miracidia (1–11 per patient) recovered from 49 patients, and tested proteins expressed from putative resistance alleles for their ability to activate OXA. We found nine mutations (four non-synonymous single nucleotide polymorphisms (SNPs), three non-coding SNPs and two indels). Both mutations (p.E142del and p.C35R) identified previously were recovered in this field population. We also found two additional mutations (a splice site variant and 1 bp coding insertion) predicted to encode non-functional truncated proteins. Two additional substitutions (p.G206V, p.N215Y) tested had no impact on OXA activation. Three results are of particular interest: (i) we recovered the p.E142del mutation from the field: this same deletion is responsible for resistance in an OXA-selected laboratory parasite population; (ii) frequencies of resistance alleles are extremely low (0.27–0.8%), perhaps due to fitness costs associated with carriage of these alleles; (iii) that four independent resistant alleles were found is consistent with the idea that multiple mutations can generate loss-of-function alleles.